Al-Hikmah Al-Muta‘Âliyyah Pemikiran Metafisika Eksistensialistik Mulla Shadra - Sholihan Sholihan (Universitas Islam Negeri Mataram, 2010)
Among the meritorious figures that develop the illuminative thought initiated by Suhrawardi is Shadr al-Dîn al-Shirazi, also known as Mulla Sadra. He is well known with his thought of al-Hikmah al-Muta'âliyyah or transcendent theosophy, an effort of harmonizing revelation, gnosis, and philosophy. He inflame an idea where the logic buried in the sea of light gnosis. He called the synthesis—one that he considered to be the particular basis of three major paths to truth for man, namely: revelation (wahy or shar'), intellection ('aql), and mystical vission (Kashf)—as al-Hikmah al-Muta‘âliyyah or transcendent theosophy. He has managed to make synthesis between deductive method of the Peripatetic, method of illumination, method of the odyssey of ‘irfân or Sufism, and method of Kalam. When his thought is compared with existentialistic thought of West, then there is a point of similarities among them not only in terms of technical language, but also in substantive matters.